Best practices for brain-compatible classrooms - Aktay, Ela (Illinois : SkyLight Professional Development, 1999)
This video programs discussed on the latest research on the psychology and physiology of the brain help students learn. This noted panel of experts offers strategies and best practices that helps to develop classroom into a brain-compatible center
Moderator, Robin Fogarty ; panelists, Geoffrey Caine, Renate Caine, Ron, Brandt, Robert Sylwester, Pat Wolfe
Keywords: Learning -- Physiological aspects; Learning; Classroom management